Criminology - Ziembo-Vogl, Joanne M. (Wadsworth/Thomson Learning, 2007)
CRIMINOLOGY: THEORIES, PATTERNS AND TYPOLOGIES, EIGHTH EDITION provides a comprehensive, in-depth analysis of all areas of criminological theory and crime typologies and effectively links criminological theory with the formulation of criminal justice policy. Renowned for its unbiased presentation of theories, issues, and controversies and its exhaustive research base, this book presents cutting-edge, seminal research, as well as up-to-the-minute policy and newsworthy examples. This edition provides students with a gateway to online and multimedia resources that capture the immediacy of the field through CNN video and an interactive, integrated Web site